2023
DOI: 10.3390/c9020048
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Heating of Activated Carbon in Microwave Field

Abstract: Activated carbon (AC) is widely utilized in water treatment, gas adsorption, and purification as well as the protection of environment due to the characteristics of prominent catalytic and adsorbent effect. The heating performances are therefore of significant importance for the further applications. The main objective of this study was therefore to detail the heating performance of activated carbon in microwave field, and the factors affecting the heating performance were also explored. In this study, the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…In contrast to traditional heating methods, microwave heating offers distinct advantages, including even heating, rapid heating rates, high efficiency, and minimal environmental impact. These attributes have gathered significant attention from researchers [10][11][12]. Moreover, microwave-assisted chemical conversion technology has emerged as a central pathway for the utilization of biomass energy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional heating methods, microwave heating offers distinct advantages, including even heating, rapid heating rates, high efficiency, and minimal environmental impact. These attributes have gathered significant attention from researchers [10][11][12]. Moreover, microwave-assisted chemical conversion technology has emerged as a central pathway for the utilization of biomass energy.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [15] concluded that mortars containing alkali-activated slag (slag to a fine aggregate ratio is 1/2.25) with NaOH solution, in different alkali dosages (4,6 and 8% by mass of Na2O) obtained better performance against AAR, under accelerated test conditions, compared to non-alkali activated mortars. For Wang and Noguchi [9], the alkaline activator acts as a key reagent of alkaline activation, being the primary source of alkali in the pore water solution, common use of NaOH, sodium silicate (Na2SiO2) or potassium hydroxide (KOH) compounds.…”
Section: Introductionmentioning
confidence: 99%